Characterization of Thermostable Cellulase from Bacillus licheniformis PANG L Isolated from the Himalayan Soil - Shyaula, Manita; Regmi, Sunil; Khadka, Deegendra; Poudel, Ram Chandra; Dhakal, Agni; Koirala, Devesh; Sijapati, Jaishree; Singh, Anjana; Maharjan, Jyoti (International Journal of Microbiology, 2023)
This study aimed to isolate, purify, and characterize a potential thermophilic cellulase-producing bacterium from the Himalayan soil. Eleven thermophilic bacteria were isolated, and the strain PANG L was found to be the most potent cellulolytic producer. Morphological, physiological, biochemical, and molecular characterization identified PANG L as Bacillus licheniformis. This is the first study on the isolation of thermostable cellulase-producing Bacillus licheniformis from the Himalayan soil. This bacterium was processed for the production of cellulase enzyme. The optimum conditions for cellulase production were achieved at 45°C after 48 h of incubation at pH 6.5 in media-containing carboxymethyl cellulose (CMC) and yeast extract as carbon and nitrogen sources, respectively, in a thermo-shaker at 100 rpm. The enzyme was partially purified by 80% ammonium sulphate precipitation followed by dialysis, resulting in a 1.52-fold purification. The optimal activity of partially purified cellulase was observed at a temperature of 60°C and pH 5. The cellulase enzyme was stable within the pH ranges of 3–5 and retained 67% of activity even at 55°C. Cellulase activity was found to be enhanced in the presence of metal ions such as Cd2+, Pb2+, and Ba2+. The enzyme showed the highest activity when CMC was used as a substrate, followed by cellobiose. The Km and Vmax values of the enzyme were 1.8 mg/ml and 10.92 μg/ml/min, respectively. The cellulase enzyme obtained from Bacillus licheniformis PANG L had suitable catalytic properties for use in industrial applications.